Understanding Platelet Thrombogenicity Cascade Of The Biodegradable Chitosan Derivatives In Von Willebrand Disease In Vitro - Periayah, Mercy Halleluyah (2015)
Chitosan has become one of the most promising local hemostatic agents because it is of particular interest as it functions independently on platelets and normal clotting mechanisms. The present study was designed with the aim to test the ability of the mechanisms of blood platelets towards the action of biodegradable chitosan in normal donors and von Willebrand disease (vWD) patients in vitro. This work determined the underlying mechanism of chitosan-induced platelet thrombogenicity and comprises experimental tests such as degradation ability; platelet: adhesion, activation: aggregation; coagulation analysis and hemostatic mediators: von Willebrand Factor (vWF), Factor 8 (FVIII), Thromboxane A2 (TXA2), P2Y12, glycoprotein IIbIIIa (GpIIbIIIa), Transforming Growth Factor- Beta 1 (TGF-β1) and Platelet Derived Growth Factor-AB (PDGF-AB). Comparative studies have been conducted to measure the hemostatic capacity of biodegradable 7% N,OCarboxymethylchitosan (NO-CMC) (with 0.45 mL collagen), 8% NO-CMC, Oligochitosan (O-C) and O-C 53.